Penerapan Lean Manufacturing Menggunakan Value Stream Mapping pada VCT Rotor di PT. XYZ - Fathimah, Amanda Nur; Winarno, Winarno (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
XYZ is an automotive component manufacturing company with two lines of production: the Shock Absorber Line and the VCT Line. One of the products on the VCT Line is the VCT rotor, with issues surrounding waste. Utilizing Lean Manufacturing approaches using the Waste Assessment Model and the Value Stream Analysis Tools is an effective way to solve issues and enhance efficiency in the VCT rotor system and production process at PT. XYZ. Total time savings as a result of the process change is 9,108.25 seconds, and the total lead time reduction in inventory is 34 days. The highest type of waste found in the VCT rotor is inventory, which accounts for 23,29% of the total waste. Overproduction contributes to 23,23% of the waste, while defect is responsible for 19,04%.